Efficacy of Tumor-Targeting Salmonella A1-R on a Melanoma Patient-Derived Orthotopic Xenograft (PDOX) Nude-Mouse Model. - Mako Yamamoto; Ming Zhao; Yukihiko Hiroshima; Yong Zhang; Elizabeth Shurell; Fritz C Eilber; Michael Bouvet; Makoto Noda; Robert M Hoffman (PLoS ONE, 2016)
Tumor-targeting Salmonella enterica serovar Typhimurium A1-R (Salmonella A1-R) had strong efficacy on a melanoma patient-derived orthotopic xenograft (PDOX) nude-mouse model. GFP-expressing Salmonella A1-R highly and selectively colonized the PDOX melanoma and significantly suppressed tumor growth (p = 0.021). The combination of Salmonella A1-R and cisplatinum (CDDP), both at low-dose, also significantly suppressed the growth of the melanoma PDOX (P = 0.001). Salmonella A1-R has future clinical potential for combination chemotherapy with CDDP of melanoma, a highly-recalcitrant cancer.